Organisation’s information security threat analysis and modelling based on a universal canvas - Makarevich, Ulad A.; Miniukovich, Katsiaryna A.; Mulyarchik, Konstantin S. (Journal of the Belarusian State University. Economics, 2021)
Security of data and information is key to the viability of an organisation. With the digitalisation of the economy, business entities need to evolve towards more effective protection of their information systems. Threat modelling helps organisations understand potential threats to information and business systems, and develop specific measures to prevent or eliminate threats. The authors review the main components of threat modelling as well as analyse and identify the shortcomings of the most commonly used modelling methods. The article proposes the author’s method based on the threat modelling canvas, that allows to eliminate the identified shortcomings. The authors have also developed and approbated an approach to teaching the use of this method.
Keywords: information security; threat modelling; threat analysis; threat modelling canvas